2013
DOI: 10.1590/1679-775720130206
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of MSH2 DNA repair protein is associated with poor prognosis in head and neck squamous cell carcinoma

Abstract: ObjectiveThis study aimed to investigate the expression of the MSH2 DNA repair protein in head and neck squamous cell carcinoma (HNSCC) in order to analyze its association with clinicopathologic factors and overall survival of patients.Material and MethodsClinical data and primary lesions of HNSSC were collected from 55 patients who underwent surgical resection with postoperative radiotherapy in Montes Claros, state of Minas Gerais, Brazil, between 2000 and 2008. Immunohistochemical reactions were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Furthermore, it has been observed that decreased expression of MSH2 gene leads to increased frequency of microsatellite instability [ 38 , 39 ]. Pereira et al [ 40 ] investigated the expression of the MSH2 DNA repair protein in HNSCC collected from 55 cases in Brazil. Patients with locoregional metastatic malignance and lower MSH2 protein levels presented worse survival.…”
Section: Role Of Dna Repair In Carcinogenesis and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been observed that decreased expression of MSH2 gene leads to increased frequency of microsatellite instability [ 38 , 39 ]. Pereira et al [ 40 ] investigated the expression of the MSH2 DNA repair protein in HNSCC collected from 55 cases in Brazil. Patients with locoregional metastatic malignance and lower MSH2 protein levels presented worse survival.…”
Section: Role Of Dna Repair In Carcinogenesis and Therapymentioning
confidence: 99%
“…Patients with locoregional metastatic malignance and lower MSH2 protein levels presented worse survival. It contributes to a higher clinic aggressiveness of HNSCC [ 40 ]. Moreover, there is a study showing that inherited MLH1 (mutL homolog 1) c.-93G>A, MSH2 c.211 + 9C>G, MSH3 c.3133G>A, and EXO1 c.1765G>A anomalies of DNA MMR pathway are essential determinants and important patient outcomes’ predictors of HNSCC, notably among smokers [ 41 ].…”
Section: Role Of Dna Repair In Carcinogenesis and Therapymentioning
confidence: 99%
“…Although multiple diagnostic and prognostic markers have been identified for both lung and head and neck cancers [18,19], the precise molecular mechanisms involved in the development and progression of these malignancies remain unclear.We understand that a functional DNA repair mechanism that includes the recognition and repair of mismatch DNA errors during DNA replication is essential in eliminating the harmful effect of several environmental risk factors, such as NNK, on the exposed cells [20][21][22][23]. A number of studies have shown that reduced expression of mismatch DNA repair (MMR) genes increases the incidence of microsatellite instability [24][25][26][27], which is often found in head and neck cancer [28][29][30][31]. Other studies have also shown that reduced expression of MSH2 or MLH1 genes at the protein or mRNA levels is associated with poor survival and MSI in lung cancer [32][33][34].In addition, MMR deficiency appears to affect the effectiveness of chemotherapy in these cancers [34,35].…”
mentioning
confidence: 99%
“…Pereira et al . reported that low expression of MSH2 DNA repair protein in HNSCCs was associated with poor prognosis 54 . These results are largely consistent with our observations and speculations.…”
Section: Discussionmentioning
confidence: 99%